Laser Speckle Reduction Using a Liquid Crystal Diffuser Enhanced with Redox Dopants. Issue 6 (8th May 2021) - Jin, Yihan; Hansford, David J.; Elston, Steve J.; Morris, Stephen M.
Abstract : Herein, a large reduction in the speckle noise is observed using a thin electroresponsive film consisting of a chiral nematic liquid crystal (LC) that has been enhanced with the addition of a redox dopant. Two different redox dopants are investigated over a range of concentrations, one being an electron acceptor and the other being an electron donor redox dopant. Results are presented that show that the incorporation of either of these dopants leads to a greater reduction in the speckle contrast than that observed using just the chiral nematic LC host when subjected to electrohydrodynamic instabilities. Furthermore, it is found that the permanent electrochemical reactions typically observed when ionic dopants, such as cetyltrimethylammonium bromide, are used are not observed for these devices, resulting in a considerable improvement in terms of the operating lifetime of the speckle reducer technology. To conclude, results that show that the speckle contrast can be reduced to C = 0.11 ± 0.02 at a temperature of 30 ºC are presented and the improvement of the quality of an image generated using a modified commercial projector fitted with a monochromatic laser source is demonstrated. Abstract : A liquid crystal diffuser that can reduce the appearance of speckle noise in laser projection and other laser‐based imaging applications is presented. Devices that contain liquid crystals that have been doped with redox dopants are found to outperform devices that contain ionic dopants or no additional dopants.